The Comparative Study Between Disney’s Mulan and BTS Fanfiction Mugunghwa: A Flower in Moonlight’s Path by Winter - Cynantia Rachmijati (Jurnal Sinestesia, 2019)
In the era of modern technology and popular culture, some fans appreciated literature by writing fanfiction. As stated by Lee (2011) it is called celebration of the media content. This aimed to describe the similarities and the dissimilarities between “Mulan” movie script and “Mugunghwa” fanfiction. The writer compared the elements by its intrinsic value based on Mufidah’s (2011). In this research the writer used qualitative method and descriptive analysis. The aspects to be analyzed were intrinsic value in general manner of the theme, character, characterization, plot, setting, point of view and style. The similarities found were the plot, point of view and characters whereas the dissimilarities were the theme, the setting and also the writing style.